Admittance‐Controlled Robotic Assistant for Fibula Osteotomies in Mandible Reconstruction Surgery. (16th November 2020) - Cheng, Lingbo; Carriere, Jay; Piwowarczyk, Jakub; Aalto, Daniel; Zemiti, Nabil; de Boutray, Marie; Tavakoli, Mahdi
Abstract : Herein, a semiautonomous robot control system for mandible reconstruction surgery is proposed. To reconstruct a segmental defect of the mandible caused by cancerous tissue, a piece of matched fibula bone is often segmented and used to replace the removed mandible section. Herein, to provide guidance to the surgeon during fibula segmentation according to the reconstruction surgical plan and improve the fibula bone cutting accuracy, an admittance‐controlled robotic assistant incorporating 3D augmented reality (AR) visualization and haptic virtual fixtures (VFs) is proposed. The admittance controller is used to reduce the surgeon's hand tremor. VF and AR are used to provide haptic and visual guidance to the surgeon, respectively. A feasibility study is conducted through a comparison of fibula osteotomies when performed with image‐guided surgery, AR‐guided surgery, VF‐guided robot‐assisted surgery, and AR‐ and VF‐guided robot‐assisted surgery. Experimental results show the effectiveness of the proposed admittance‐controlled robotic assistant with AR and VF compared with the other three methods. The proposed method is found to be able to increase precision of the osteotomized segments with a lower average linear variation of 1.04 ± 0.79 mm and a lower average angular variation of 1.83 ± 1.85° compared with the virtual preoperative plan. Abstract : An admittance‐controlled robotic assistant incorporating 3D augmented reality (AR) visualization and haptic virtual fixtures (VFs) is demonstrated to play a positive role for fibula osteotomies in mandible reconstruction by providing guidance to the surgeon during fibula segmentation according to the reconstruction surgical plan and improving the fibula bone cutting accuracy.